Maximizing Safety in Clinical and Translational Research - Sugarman, Jeremy (IRB, 2013)
Clinical and translational research necessarily involves some risks to human subjects. Moreover, early-phase research is conducted primarily to determine the safety of interventions that are potentially risky. Despite such inherent risks, research should not pose avoidable risks. Although considerable attention in the design and review of research focuses on considering its risks and benefits, this may be insufficient for robustly protecting the interests of those who decide to participate in clinical and translational research, as is exemplified by the TGN1412 study. While multiple definitions for these types of research exist, here clinical research denotes research taking place in clinical settings that involves the testing of biomedical interventions for safety and efficacy. Here, Sugarman talks about the importance of maximizing safety in clinical and translational research.